THE AGREEMENT FOR THE RESULTS OF THE AGRICULTURAL LAND IN THE INDIGENOUS PERSPECTIVE OF GORONTALO - Johan Jasin (Indonesia Prime, 2016)
The agreement for the results of the agricultural land in Indonesia, it is a custom, not affected by globalization that prioritizes a written document. This custom interesting to be listened to with a focus on description form, contents and implementation. The study of this nature is a socio legal research using an approach of philosophical sociology and law, who viewed the practice of overriding high society, while the primary data source is the custom figures as informants and the secondary data source is legislation, literature and research results. The data collected is analyzed using qualitative techniques. The results showed that: the agreements for agricultural land results in Gorontalo, between landowners and tenants are conducted orally, in which the rights and obligations of each party, the risks, the length of time, and forms the Division results depend on both sides negotiating with upholding the values of trust, honesty, sense of community and tradition. As for how the Division according to the custom are: (a) the seasonal crops such as maize, the landowner has a third section while the tenants enjoy the accounting section; (b) the perennials such as bananas, the respective parties (owners and tenants) got equal parts namely ½ part; (c) the annual plants such as coconut, accounting (2/3) is part of the rights of landowners, while tenants obtain one third (1/3), parts.